A fidelidade em cooperativas: um estudo em organizações de agricultores familiares no Rio Grande do Sul - Peroni, Neimar Damian (2018)
The study addressed loyalty, as opposed to opportunism, in 186 family farmer cooperatives participating in the “Programa de Extensão Cooperativa” (PEC) in the state of Rio Grande do Sul, Brazil. It was realized through intercession between instrumental and substantive rationalities. In order to do so, it used conceptual theorical elements of the Social Capital Theory and the Transaction Costs Economy. The methodology used was a case study with multiple analysis units. The main methodological procedures were the analysis of PEC documents prepared by program consultants, participant observation and focal interviews. Within the specific objectives, the study characterized the 186 cooperatives, representing 43.900 members, with 77% of family farmers, in the following categories of analysis: a) productive chains: leading milk in 65 units, diversified food production in 51, horticultural in 44 and grain production in 32 establishments; in the effective inclusion of family farmers by chain: 15.300 milk farmers, 13.700 grain farmers, 6.600 diversified food and 2.100 meats, b) the age range of the enterprises: the predominance of young organizations with fewer members and that work mainly in local or regional short supply chains or in the dairy industry; c) real estate infrastructure: only 46% of the enterprises have properties, 39% have precarious possession by assignment or rent and 15% of the organizations do not own or occupy real estate, functioning "virtually". As for the general objective of the thesis, the existence of organizations with supervenience of different types of rationalities and that of different way, approach the loyalty of its associates and minimization of the opportunism. The typification was idealized in (1) "instrumental cooperatives", (2) "substantive cooperatives", or with equivalence in actions called "hybrid cooperatives". In the occurrences and scope, the order was (1) (3) (2), in the performance of the organizational management and in the proportion of active associates (2) (3) (1). In addition, the actions and mechanisms developed to establish loyalty in each organizational type were included.